The 1927 Silungkang Rebellion in a Historiographical Review - Sari, Monika Aprila; Asnan, Phil Gusti; Nopriyasman, Nopriyasman (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study examines the 1927 Silungkang Rebellion in a Historiographical Review. The historiographical review was conducted on three works specifically discussing the Silungkang Rebellion written by Indonesians. This study uses a content analysis method. This method is used to identify the content of an event. The results of this study from the three works studied show differences in the background and education of the authors. Some are academic writers and amateur writers, while in terms of education, some are elementary school graduates, Doctorates (S3), and high school. Based on these differences, they influence the resulting works, especially in writing and how the authors provide their views and interpretations of the work. In addition, in the work there are two eras: the author's era (the New Order and Reformation eras) and the war era, when the event occurred, which was the colonial era.